Startups and Spinoffs as Factors of the Academic Business Development: the Foreign Experience and the Ukrainian Prospects - Novikova, I.E.; Osetskiy, V.L.; Alekseieva, K.A. (Science and Innovation, 2024)
Introduction. Modern, equipped with cutting-edge technologies universities are a perfect environment for creating the primary atmosphere of innovative business climate. Problem Statement. The implementation of modern, profitable innovation projects (startups or spinoffs) in the form of small innovative enterprises is a new way of successful commercialization of promising ideas. Universities are perfect site for launching the first startup ideas. Purpose. To study the trends of academic business development in the context of increasing importance of innovation activities, in particular, the role of startups and spinoffs in the activities of foreign and Ukrainian universities. Materials and Methods. There has been used the comparison of world universities ratings. The SWOT-analysis of the prospects of startup and spinoff projects has been carried out based on the universities of Ukraine. Analysis of dependence of the proceeds from innovative achievements on the costs of R&D works has been made. Results. A comparative overview of the trends in the development of academic business abroad and in Ukraine has been made. The national and European legislation in the sphere of formation of R&D products has been analyzed. The factors that sufficiently hamper the development of innovative process in Ukraine have been identified. Recommendations concerning popularizing the innovative and investment activities and establishing fruitful international cooperation have been given. Conclusions. The obtained results enable formulating the principles for the formation of a new methodological paradigm for intellectual assets management in universities taking into account the peculiarities of the development of national science, economy, entrepreneurship, and high-tech market.